Natural Theology. - Paley, William (Oxford world's classics., 2006)
In Natural Theology William Paley set out to prove the existence of God from the evidence of the beauty and order of the natural world. This edition reprints the original text of 1802, and sets the book in the context of the theological, philosophical, and scientific debates of the nineteenth century. - ;'The consciousness of knowing little, need not beget a distrust of that which he does not know.'. In Natural Theology William Paley set out to prove the existence of God from the evidence of the beauty and order of the natural world. Famously beginning by comparing the world to a watch, whose.